Factors affecting adult feeding in a Drug rehabilitation Center - Troncoso Pantoja, Claudia (2016)
Objective: To interpret the perception of the determining factors that influence the diet of a group of intern patients in a drug rehabilitation center in Concepción, Chile, during the year 2015. Materials and methods: Through a qualitative design with a phenomenological approach, intern patients of a drug rehabilitation facility, who fulfilled the study assigned criteria, were interviewed. The collection of data was conducted through semi structured interviews; which were validated by experts and subject to a pilot test. Nonprobability convenience sampling was performed. The sample size was determined through theoretical saturation, which was completed at the eighth interview. The results were subject to triangulation of informants, and were analyzed using the technique of discourse analysis. Results: The participants identify positive and negative factors that condition their diet. They claim that having a fixed schedule is positive since this helps them to have a more organized diet. However, some stressful situations within the facilities are described as limiting factors in their mood, thus affecting their appetite and reducing their food intake. Additionally, not being with their families, especially at the beginning of the treatment, is considered a negative aspect. The lack of variety in terms of food preparation is also negative since this does not correspond to their food preferences. During the drug withdrawal stage, the intake of food containing carbohydrates of rapid absorption was increased. Conclusions: It is interpreted that the interviewees at the drug rehabilitation facility identify conditioning factors that influence their diet, which promote or inhibit food intake, and affect the attitude they present towards their diet in the drug withdrawal stage.